A CASE OF METHANOL INTOXICATION COMPLICATED WITH ACUTE PANCREATITIS, ALCOHOLIC KETOACIDOSIS, AND INTRACEREBRAL HEMORRAGE - Rahardi, Eric; Moda Arsana, Putu (journal of internal medicine, 2012)
Methanol intoxication occurs after accidental or suicidal ingestion occasionally and the toxicity is due to the formation of formaldehyde and formic acid. Methanol ingestion can also lead to acute pancreatitis, a sudden in! ammation of the pancreas, and high metabolic acidosis as a complication. Brain injury in methanol intoxication could be ischemia or hemorrhage form. Therefore we?d like to present a report a male with methanol intoxication with several complication such, acute pancreatitis, alcoholic ketoacidosis, and CVA-ICH. The patient presented with hemodynamic instability and severe metabolic acidosis with pH 6.991. The anion gap was 30 mmol/l. Amylase was 187 U/l and CT scan showed intracerebral hemorrhage at right fronto temporo parietal lobe with peri-focal edema (volume 48 cc). Patient unfortunately died three days later after force discharge by his families. Brain injury in methanol toxicity is characterized by lesions affecting both basal ganglia and subcortical regions. The lesion could be ischemia/necrosis or hemorrhage, selectively affecting the putamenal bilaterally.
Keywords: Methanol intoxication, acute pancreatitis, brain injury